Diversity and distribution of Lentibulariaceae in Bahia state, Brazil: implications for phytogeography and conservation - Guedes, Felipe Martins; Oliveira Miranda, Vitor Fernandes [UNESP]; Alves, Marccus (Magnolia Press, 2022)
Bahia state harbours an immense diversity of plant species with several cases of endemism, especially in the savanna wetlands, typical ecosystems where most Lentibulariaceae representatives occur. In this context, we aimed to improve the characterization of these savanna wetlands in terms of species richness of Lentibulariaceae, their phytogeographic patterns, endemism, forms of rarity, threats to their habitats, and conservation efforts. Herein we present the synopsis of the 42 species of Lentibulariaceae that occur in Bahia state, providing short diagnostic characterization, photographs of living specimens, updated geographic distribution displayed in maps, new records, and discussion concerning phytogeographic patterns, endemism, rarity, habitat characterization and current scenario of threats and conservation. Our results show a disjunct distribution and similarity in Lentibulariaceae species composition between savanna wetlands, corroborating previous hypotheses of vegetation connections during moister climatic conditions in the past. Moreover, differences in species composition among different restinga areas are consistent with biogeographical and paleomodelling studies pointing the São Francisco River as a geographic barrier influencing speciation and genetic diversity. Finally, we emphasize the situation of abandonment in some Protected Areas, lacking proper infrastructure, managers, management plans and board, and insufficient results for the effective conservation and protection of the environment and species.
Keywords: Carnivorous plants; conservation; distribution patterns; Genlisea; savanna wetlands; Utricularia